A comprehensive assessment of breast and cervical cancer control infrastructure in Zambia. (September 2017) - Chibwesha, Carla; Pinder, Leeya F.; Musonda, Agnes; Sikombe, Kombatende; Matambo, Jane; Bateman, Allen C.; Mershon, Claire-Helene; Mwanahamuntu, Mulindi; Kapambwe, Sharon; Lishimpi, Kennedy; Parham, Groesbeck P.
Highlights: The project aimed to quantify service delivery capacity for breast and cervical cancer throughout Zambia. We assessed human resource and facility infrastructure available for breast and cervical cancer care. The results provide an overview of available services for breast and cervical cancer in Zambia. Our report further highlights the important cancer control gains that have been made in Zambia. The Ministry of Health and other stakeholders have demonstrated commitment to reduce the burden of these malignancies. Abstract: Introduction: By 2030 cancer will kill one million Africans each year. Women will bear the heaviest burden, as cancers of the breast and cervix are the most common malignancies and causes of cancer-related death in the African region. National-level data that map the status of women's cancer control services are needed to inform strategies for implementing platforms for the early detection and treatment of these "priority" cancers. Methods: Using mixed-methods, we assessed available services for breast and cervical cancer detection and treatment at all provincial hospitals, the national referral hospital, and the national cancer treatment center in Zambia. Results: A system for cervical cancer prevention using visual inspection with acetic acid (VIA) and ablation/excision of precancerous lesions has been established at the provincial level. The potential for mammography, clinical breast examination, diagnostic ultrasound and biopsy exist at the provincial level, albeit on a much smaller scale. Breast wedge resections and mastectomy can be performed in provinces where general surgeons are located; however, breast conserving and reconstructive surgery are not available. Invasive cancers are generally referred to University Teaching Hospital in Lusaka, where services for radiation, chemotherapy and hormonal therapy are available but overburdened. Pathology services nationwide are woefully inadequate. Discussion: The assessment revealed a critical need for centrally coordinated, but decentralized, public service platforms for women's cancer control. Efforts are underway, through multiple stakeholders, to implement recommendations related to training healthcare workers who can provide advanced diagnostic and therapeutic services, improving pathology services, and innovative financing for these initiatives.